Analysis of Vitamin C and Iron (Fe) Content in Moringa Leaf Jelly - Ata, Hilda Rambu Bangi; Adu, Apris A.; Nur, Marselinus Laga (Timorese Journal of Public Health, 2020)
Vitamin C deficiency can trigger iron deficiency and these nutritional problems can contribute to an increase in the number of malnutrition cases and malnutrition. In response to the problem of iron deficiency, the government of East Nusa Tenggara runs various programs, including the provision of supplements in the form of iron tablets. Another effort is to carry out the Supplemental Feeding Program (SFP). The standard formula given by the World Health Organization (WHO) consists of milk, oil, powdered sugar, and water. The modification formula that is quite dense energy and protein consists of materials that are easily available in society at an affordable price. In the international world, the cultivation of moringa leaves is a program that is being promoted, including the province of NTT, one of them. With the processing of moringa leaves into a snack food that is liked by all circles, it will increase the utilization of moringa leaves in society so that the nutritional content of moringa leaves can be absorbed by the body. Jelly drink is expected to be an alternative to fruit juice drink that can improve the stability of fruit juice because this drink has a gel consistency so it can avoid deposition, but easy to drink. This study is a Quasi Experiment using Complete Randomized Design (CRD) which intentionally adds moringa flour to existing making recipes jelly with 3 different concentrations. Data analysis used One-Way Anova Test to see the difference in Vitamin c and Iron levels at each concentration jelly. The results of the One-Way ANOVA test showed that there was an average difference in the concentration of iron and Vitamin C in the jelly with the addition of moringa flour in the composition of 50%, 40%, and 30% (sig = 0.00 <pvalue 0.05).